Instantaneous gelation in coagulation dynamics - Costa, Fernando Pestana da (1992)
The coagulation equations are a model for the dynamics of cluster growth in which clusters can coagulate via binary interactions to form larger clusters. For a certain class of rate coefficients we prove that the density is not conserved on any time interval.